2015
DOI: 10.3892/mmr.2015.4152
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and apoptogenic effects of Strobilanthes crispa Blume extracts on nasopharyngeal cancer cells

Abstract: The chemotherapeutic agents used to treat nasopharyngeal cancer (NPC) exhibit low efficacy. Strobilanthes crispa Blume is widely used for its anticancer, diuretic and anti‑diabetic properties. The present study aimed to determine the cytotoxic and apoptogenic effects of S. crispa on CNE‑1 NPC cells. A 3‑(4,5‑dimethylthiazol‑2‑yl)‑2,5 diphenyl tetrazolium bromide assay was used to evaluate the cytotoxic effects of S. crispa against CNE‑1 cells. The rate of apoptosis was determined using propidium iodide stainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…A previous study demonstrated that S. crispa leaves possess anti-diabetic, diuretic and blood pressure lowering properties (17). Furthermore, a number of studies have recorded the potency of S. crispa extracts in inhibiting cancer cell growth (22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study demonstrated that S. crispa leaves possess anti-diabetic, diuretic and blood pressure lowering properties (17). Furthermore, a number of studies have recorded the potency of S. crispa extracts in inhibiting cancer cell growth (22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…In colon cancer cell lines, 50 % death was induced by a very low concentration of S. virendrakumarana shoot extract with a value of 111.99±4.91 µg/ml. In the previous studies, five different leaf extracts of S. crispus (hexane, chloroform, ethyl acetate, methanol, and aqueous) in CNE-1 cells, the ethyl acetate extract showed the strongest anti-proliferative effect on the cells with an LC 50 value of 119.00±48.10 µg/ml [19] . The antiglycolytic activities of S. crispus fraction and its bioactive components on triple-negative breast cancer cells (MDA-MB-231) are attributed to the bioactivity of the plant [20] .…”
Section: Resultsmentioning
confidence: 87%
“…The results of in vitro xanthine oxidase inhibition assay of some selected gout medicinal plants from Indonesia was summarized in The Strobilanthes crispa L. Blume leaves, known as keji beling in Indonesia, have been reported to have many pharmacological activities, including as anti-hyperglycemic, anti-oxidant, antimicrobial, wound healing anti-cancer on breast, liver cervical, lung, prostate and nasopharyngeal cancer, anti-inflamatory, antitrypanosomal, anti-obesity [31][32][33][34][35][36][37]. However, the research on the Strobilanthes crispa L. Blume leaves as an anti-hyperuricemia has never been studied before, thus, it in necessary to do further research regarding the potential of this plant to be a gout medicine.…”
Section: Resultsmentioning
confidence: 99%